Human β-Defensin 2 Mutations Are Associated With Asthma and Atopy in Children and Its Application Prevents Atopic Asthma in a Mouse Model - Borchers, Natascha S.; Santos-Valente, Elisangela; Toncheva, Antoaneta A.; Wehkamp, Jan; Franke, Andre; Gaertner, Vincent D.; Nordkild, Peter; Genuneit, Jon; Jensen, Benjamin A. H.; Kabesch, Michael (Frontiers in Immunology, 2021)
Asthma and allergies are complex, chronic inflammatory diseases in which genetic and environmental factors are crucial. Protection against asthma and allergy development in the context of farming environment is established by early animal contact, unpasteurized milk consumption and gut microbiota maturation. The human β-defensin 2 (hBD-2) is a host defense peptide present almost exclusively in epithelial tissues, with pronounced immunomodulatory properties, which has recently been shown to ameliorate asthma and IBD in animal models. We hypothesized that adequate hBD-2 secretion play a role protection against asthma and allergy development and that genetic variation in the complex gene locus coding for hBD-2 may be a risk factor for developing these diseases, if as a consequence, hBD-2 is insufficiently produced. We used MALDI-TOF MS genotyping, sequencing and a RFLP assay to study the genetic variation including mutations, polymorphisms and copy number variations in the locus harboring both genes coding for hBD-2 (DEFB4A and DEFB4B). We administered hBD-2 orally in a mouse model of HDM-induced asthma before allergy challenge to explore its prophylactic potential, mimicking a protective farm setting. Despite the high complexity of the region harboring DEFB4A and DEFB4B we identified numerous genetic variants to be associated with asthma and allergy in the GABRIELA Ulm population of 1,238 children living in rural areas, including rare mutations, polymorphisms and a lack of the DEFB4A. Furthermore, we found that prophylactic oral administration of hBD-2 significantly curbed lung resistance and pulmonary inflammation in our HDM mouse model. These data indicate that inadequate genetic capacity for hBD-2 is associated with increased asthma and allergy risk while adequate and early hBD-2 administration (in a mouse model) prevents atopic asthma. This suggests that hBD-2 could be involved in the protective farm effect and may be an excellent candidate to confer protection against asthma and allergy development.